Randomised controlled double-blind non-inferiority trial of two antivenoms for saw-scaled or carpet viper (Echis ocellatus) envenoming in Nigeria. - Isa S Abubakar; Saidu B Abubakar; Abdulrazaq G Habib; Abdulsalam Nasidi; Nandul Durfa; Peter O Yusuf; Solomon Larnyang; John Garnvwa; Elijah Sokomba; Lateef Salako; R David G Theakston; Ed Juszczak; et al. (Public Library of Science (PLoS), 2010)
BACKGROUND: In West Africa, envenoming by saw-scaled or carpet vipers (Echis ocellatus) causes great morbidity and mortality, but there is a crisis in supply of effective and affordable antivenom (ISRCTN01257358). METHODS: In a randomised, double-blind, controlled, non-inferiority trial, "EchiTAb Plus-ICP" (ET-Plus) equine antivenom made by Instituto Clodomiro Picado was compared to "EchiTAb G" (ET-G) ovine antivenom made by MicroPharm, which is the standard of care in Nigeria and was developed from the original EchiTAb-Fab introduced in 1998. Both are caprylic acid purified whole IgG antivenoms. ET-G is monospecific for Echis ocellatus antivenom (initial dose 1 vial) and ET-Plus is polyspecific for E. ocellatus, Naja nigricollis and Bitis arietans (initial dose 3 vials). Both had been screened by pre-clinical and preliminary clinical dose-finding and safety studies. Patients who presented with incoagulable blood, indicative of systemic envenoming by E. ocellatus, were recruited in Kaltungo, north-eastern Nigeria. Those eligible and consenting were randomly allocated with equal probability to receive ET-Plus or ET-G. The primary outcome was permanent restoration of blood coagulability 6 hours after the start of treatment, assessed by a simple whole blood clotting test repeated 6, 12, 18, 24 and 48 hr after treatment. Secondary (safety) outcomes were the incidences of anaphylactic, pyrogenic and late serum sickness-type antivenom reactions. FINDINGS: Initial doses permanently restored blood coagulability at 6 hours in 161/194 (83.0%) of ET-Plus and 156/206 (75.7%) of ET-G treated patients (Relative Risk [RR] 1.10 one-sided 95% CI lower limit 1.01; P = 0.05). ET-Plus caused early reactions on more occasions than did ET-G [50/194 (25.8%) and 39/206 (18.9%) respectively RR (1.36 one-sided 95% CI 1.86 upper limit; P = 0.06). These reactions were classified as severe in 21 (10.8%) and 11 (5.3%) of patients, respectively. CONCLUSION: At these doses, ET-Plus was slightly more effective but ET-G was slightly safer. Both are recommended for treating E. ocellatus envenoming in Nigeria. TRIAL REGISTRATION: Current Controlled Trials ISRCTN01257358.